Enhanced combustion and emission characteristics of diesel-algae biodiesel-hydrogen blends in a single-cylinder diesel engine - Hariram V; Sathishbabu R; Godwin John J; Nandagopal Kailiappan; Vijayakumar K; Sangeeth Kumar E; Kamakshi Priya K (Results in Engineering)
With the escalating global energy demand, the pursuit of sustainable energy sources has become increasingly urgent. Among these, biofuels have gained significant attention for their potential to provide renewable and eco-friendly alternatives. Biodiesel is recognized for its diverse and cost-effective feedstock options. The study provides a novel approach to the production of biodiesel by employing the use of Dunaliella salina microalgae as a green source. The research suggests the blends provide a future solution to less toxic fuel sources, achieving efficiency and minimizing emissions. This research emphasize on the production of biodiesel from Dunaliella salina microalgae, a promising resource due to its high energy yield. The microalgae were cultivated in an f/2 nutrient medium enriched with carbon dioxide, vitamins, and trace metals. A total of 700 mL of bio-oil was extracted using ultrasonication at 50 Hz for 85 minutes. Then, the bio-oil was transesterified in a single-stage, sodium hydroxide-catalysed process with methanol as a solvent. The process yielded a high extraction efficiency of 94 %. The produced biodiesel was characterized through advanced analytical techniques, including NMR spectroscopy, GC-MS, and FTIR test studies, confirming its suitability as a fuel. Combustion and emission analyses revealed that the direct substitution of biodiesel blends for diesel in engines significantly reduced hydrocarbon and carbon monoxide emissions, although a slight increase in nitrogen oxide (NOx) emissions was noted. The combustion and emission characteristics were influenced by blend composition and calorific value. Additionally, the study provides a detailed comparison of the performance of pure diesel, biodiesel blends, and hydrogen-enriched biodiesel in diesel engines, offering valuable insights into their environmental and performance impacts. This study gives additional insights towards future work such as scalability (consisting large scale cultivation of algae for better studies), engine durability (studies on engine wear and tear) and integration with renewable energy sources (integrating renewable sources like solar and wind energies).